COVID-19 and dys-regulation of pulmonary endothelium: implications for vascular remodeling. (February 2022) - Jadaun, Pavitra K.; Chatterjee, Suvro
Abstract: Coronavirus disease-2019 (COVID-19), the disease caused by severe acute respiratory syndrome-coronavirus-2, has claimed more than 4.4 million lives worldwide (as of 20 August 2021). Severe cases of the disease often result in respiratory distress due to cytokine storm, and mechanical ventilation is required. Although, the lungs are the primary organs affected by the disease, more evidence on damage to the heart, kidney, and liver is emerging. A common link in these connections is the cardiovascular network. Inner lining of the blood vessels, called endothelium, is formed by a single layer of endothelial cells. Several clinical manifestations involving the endothelium have been reported, such as its activation via immunomodulation, endotheliitis, thrombosis, vasoconstriction, and distinct intussusceptive angiogenesis (IA), a unique and rapid process of blood-vessel formation by splitting a vessel into two lumens. In fact, the virus directly infects the endothelium via TMPRSS2 spike glycoprotein priming to facilitate ACE-2-mediated viral entry. Recent studies have indicated a significant increase in remodeling of the pulmonary vascular bed via intussusception in patients with COVID-19. However, the lack of circulatory biomarkers for IA limits its detection in COVID-19 pathogenesis. In this review, we describe the implications of angiogenesis in COVID-19, unique features of the pulmonary vascular bed and its remodeling, and a rapid and non-invasive assessment of IA to overcome the technical limitations in patients with COVID-19. Graphical Abstract: ga1 Highlights: Implications of intussusceptive angiogenesis in COVID-19. Cytokine storm and its implications in the remodelling of pulmonary vascular bed. Silent pulmonary hypoxia as a hallmark of COVID-19. A rapid and non-invasive assessment of intussusceptive angiogenesis to overcome the technical limitations in Covid-19 patients.